Drought response strategies and hydraulic traits contribute to mechanistic understanding of plant dry-down to hydraulic failure. (16th March 2019) - Blackman, Chris J; Creek, Danielle; Maier, Chelsea; Aspinwall, Michael J; Drake, John E; Pfautsch, Sebastian; O'Grady, Anthony; Delzon, Sylvain; Medlyn, Belinda E; Tissue, David T; Choat, Brendan
Abstract: Drought-induced tree mortality alters forest structure and function, yet our ability to predict when and how different species die during drought remains limited. Here, we explore how stomatal control and drought tolerance traits influence the duration of drought stress leading to critical levels of hydraulic failure. We examined the growth and physiological responses of four woody plant species (three angiosperms and one conifer) representing a range of water-use and drought tolerance traits over the course of two controlled drought–recovery cycles followed by an extended dry-down. At the end of the final dry-down phase, we measured changes in biomass ratios and leaf carbohydrates. During the first and second drought phases, plants of all species closed their stomata in response to decreasing water potential, but only the conifer species avoided water potentials associated with xylem embolism as a result of early stomatal closure relative to thresholds of hydraulic dysfunction. The time it took plants to reach critical levels of water stress during the final dry-down was similar among the angiosperms (ranging from 39 to 57 days to stemP88 ) and longer in the conifer (156 days to stemP50 ). Plant dry-down time was influenced by a number of factors including species stomatal-hydraulic safety margin ( g s P90 – stemP50 ), as well as leaf succulence and minimum stomatal conductance. Leaf carbohydrate reserves (starch) were not depleted at the end of the final dry-down in any species, irrespective of the duration of drought. These findings highlight the need to consider multiple structural and functional traits when predicting the timing of hydraulic failure in plants.